Stimuli-responsive polymer composites for fabric applications - A.H, Bhat; Imran, Khan; Showkat, Ahmad Bhawani; U, Gazal (Woodhead Publishing, 2021)
Stimuli-responsive polymers are materials that can display remarkable changes in their properties with slight change in environmental conditions. Substantial change in the structure and properties can be made to the textiles by the incorporation of smart polymers into them. The following characteristics for intelligent polymers viz., thermal-, moisture-, and light-responsive polymers, and thermal- and pH-responsive hydrogels, have been incorporated into the fabrics to improve or achieve smart fabric functionalities. The functional components include esthetic appeal, comfort, drug release, fantasy design (color changing), wound monitoring, smart wetting properties, and protection against tough environmental alterations. In this chapter, the applications of stimuli-responsive polymer/composites in fabrics and the clothing field have been deliberated upon; the related issues on the fabrication of clothing and their potential applications in the years to come are elucidated.